Recent Vertebrate Carcasses and Their Paleobiological Implications. - Weigelt, Johannes, 1890-1948 (University of Chicago Press, 2009)
The first English translation of Johannes Weigelt's 1927 classic makes available the seminal work in taphonomy, the study of how organisms die, decay, become entombed in sediments, and fossilize over time. Weigelt emphasized the importance of empirical work and made extensive observations of modern carcasses on the Texas Gulf Coast. He applied the results to evidence from the fossil record and demonstrated that an understanding of the postmortem fate of modern animals is crucial to making sound inferences about fossil vertebrate assemblages and their ecological communities. <BR.